thesis journal Analysis of Slam Tehcniques for Point Acquisition in Sambo Martial Arts Athletes in Semarang City - Rais, Rifzki; Setyawati, Henny; Nasuka, Nasuka (Journal of Physical Education and Sports, 2023)
The slam technique is one of the techniques in Sambo that produces the most points. There are some athletes who do not understand the slam technique, so it is necessary to practice. There are 5 slam techniques, namely slamming legs, hands, neck, hips and dropping. The purpose of this study was to find out how to improve the ability of slam techniques, knowing the effect of training and the effectiveness of slam techniques, and which slam techniques were most effective on Sambo athletes in Semarang City.This study uses a mixed methods approach and the method used is comparative-descriptive. The data collection technique uses qualitative interviews, while the quantitative uses direct tests on athletes to take the points obtained by Sambo athletes in Semarang City. The results showed that how to improve the ability of the Sambo slam technique with verbal communication (instructions and directions) and nonverbal trainers (demonstrating and drill exercises), there was an effect of kickback technique training on the acquisition of points (the percentage increase from the previous exercise included 23% for the first exercise, 32 % for the second exercise, 17% for the third exercise, and 18% for the fourth exercise.The results of the third study are the order of effectiveness, namely hands (2.3) > hips (2.25) > feet (2.17) > dropping down (2 .09) > neck (1.76). Of the five slam techniques the most effective was the hand kick with 32.79% points, then leg kick 24.77%, neck kick 15.37%, hip kick 14.91 %, and the last technique is flopped with a percentage point of 12.16%.